The magic sticks, and other plays - Yates, Irene (Heinemann Educational Oxford, 1999)
The Magic Sticks and Other Plays is a collection of plays by Nigerian writer, Wole Soyinka, known for his mastery of African folklore, drama, and socio-political commentary. The book consists of short plays that explore themes of tradition, morality, and the supernatural, often incorporating elements of Yoruba culture. The title play, The Magic Sticks, revolves around a magical occurrence that disrupts a community, reflecting on power dynamics, justice, and human nature. Each play in the collection presents engaging characters and insightful narratives that provoke thought and entertain audiences.